Successful Treatment of Pediatric Acute Myeloid Leukemia Presenting with Hyperbilirubinemia Secondary to Myeloid Sarcoma: A Case Report - Hwazen A. Shash; Ashraf M. Khairy (MDPI AG, 2022)
Myeloid sarcoma (MS), a tumor consisting of myeloid blasts with or without maturation, occurs at anatomical sites other than the bone marrow. MS of the gastrointestinal tract presenting with jaundice in children is rare. We report the case of a 4-year-old boy with a 6-week history of symptoms of obstructive jaundice due to a peripancreatic mass compressing the common bile duct. Six weeks later, blasts were found in a peripheral smear prior to surgical biopsy; bone marrow evaluation and flow cytometry results led to a diagnosis of acute myeloid leukemia (AML) with MS. No further invasive testing or temporary drainage was performed. He was started on induction therapy with full therapeutic doses of cytarabine, dose reductions of etoposide, and escalating doses of daunorubicin. His liver enzymes normalized, and he completed subsequent cycles of chemotherapy with full doses. The abdominal ultrasound showed resolution of the mass after the second cycle of chemotherapy. He is currently in remission three years after completing therapy. AML-directed chemotherapy in patients with obstructive jaundice secondary to MS may be beneficial without requiring invasive testing or temporary drainage procedures. Daily follow-up is crucial for chemotherapy dose modifications. Management plans should be individualized according to the patient's clinical condition.